Impact of COVID-19 on social determinants of health for adults with cystic fibrosis. (August 2021) - Albon, Dana; Bruschwein, Heather; Soper, Morgan; List, Rhonda; Jennings, Deirdre; Gettle, Lucy; Compton, Martina; Bailey, Molly; Starheim, Elissa; Murray, Rachel; Kalmanek, John; Somerville, Lindsay
Introduction: Outcomes in cystic fibrosis are influenced by multiple factors, including social determinants of health. Low socioeconomic status has been shown to be associated with lung function decline, increased exacerbation rates, increased health care utilization, and decreased survival in cystic fibrosis. The COVID-19 pandemic disrupted the US economy, placing people with cystic fibrosis at risk for negative impacts due to changes in social determinants of health. Methods: To characterize the impact of COVID-19-related changes in social determinants of health in the adult cystic fibrosis population, a social determinants of health questionnaire was designed and distributed to patients as part of a quality improvement project. Results: Of 132 patients contacted, 76 (57.6%) responses were received. Of these responses, 22 (28.9%) answered yes to at least one question that indicated an undesired change in social determinants of health. Patients with stable employment prior to COVID-19 were more likely to endorse undesired change in all domains of the questionnaire, and the undesired changes were most likely to be related to employment, insurance security, and access to medications. Patients receiving disability were more likely to report hardship related to utilities and food security compared with patients previously employed or unemployed. Of patients endorsing risk of socioeconomic hardship, 21 (95.5%) were contacted by a social worker and provided resources. Conclusion: Utilizing a social determinants of health questionnaire to screen for social instability in the context of COVID-19 is feasible and beneficial for patients with cystic fibrosis. Identifying social issues early during the pandemic and implementing processes to provide resources may help patients with cystic fibrosis mitigate social hardship and maintain access to health care and medications.